Senior High School Learning Motivation on Physics Subject - Nurmalita Sari; Widha Sunarno; Sarwanto (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
Learning motivation is students’ willingness to study that comes from within. The objective of this research was to find out Senior High School students’ learning motivation level for physics subject. The subjects of this research were 60 students from Science Class of Senior High School 5 Surakarta who were randomly selected. A questionnaire was used as an instrument to measure students’ learning motivation. The result showed that students’ learning motivation in physics subject was categorized as medium level with an average score of 20.42. The percentage for each aspect was as follows: attention (24.33%), relevance (24.98%), confidence (24.33%), and satisfaction (25.71%).